(untitled) (Al-Qamar, 2021)
The translation is a cross-cultural and cross-linguistic activity that deals with the transfer of linguistic signs, codes, and terms of one language to another. It considers the cultural norms in this transferring activity. The translation is a science that took the lives of translators on the deck burning alive, killing brutally, and slaughtering which according to the current definitions of terrorism, are the worst kinds of Terrorism. The article deals with the terrorism due to translations causing the death of translators and readers and other innocent people. It, as well, deals with the use of translation for terrorist activities.